Genomic instability and cancer: lessons from analysis of Bloom's syndrome. (20th May 2009) - Payne, Miranda; Hickson, Ian D.
Abstract : Bloom's syndrome (BS) is a rare autosomal recessive disorder characterized by genomic instability and cancer predisposition. The underlying genetic defect is mutation of the BLM gene, producing deficiency in the RecQ helicase BLM (Bloom's syndrome protein). The present article begins by introducing BLM and its binding partners before reviewing its known biochemical activities and its potential roles both as a pro-recombinase and as a suppressor of homologous recombination. Finally, the evidence for an emerging role in mitotic chromosome segregation is examined.